Implementation of Clustering on Tobacco Import Data By Country Of Destination Using The K-Means Algorithm - Syifa Aisyah Rahmah Sibuea; M. Safii (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
Tobacco is a seasonal agricultural product which is not a food commodity, but a plantation commodity. This product is consumed not for food but as a spare time filler or